Improving the quality of Community Health Centres services in Province of Jambi: an integrated quality management model based on the European Foundation Quality Management (EFQM) and Six Sigma - Amri Amir; Tona Aurora Lubis; Junaidi Junaidi; Dwi Noerjoedianto; Andi Subandi (Universitas Aisyah Pringsewu, 2023)
The quality of health services is essentially required to achieve the optimal health status through community-based policies by prioritizing prevention and promotion at the primary healthcare level. However, the deficient quality of healthcare services has been a complicated problem in the public health sector that must be solved immediately. Practically, there are four aspects of quality management, including management, infrastructure, core, and the quality of Community Health Centres (CHSs) services. This study aims to develop a quality management model at 24 CHCs in Province of Jambi using the EFQM and Six Sigma model. The questionnaire was used to collect data from 560 health workers and analysed using a second-order model of Smart PLS software. The research found that the implementation of four aspects in quality management was classified as a good category. The aspects were statistically associated with the quality of the CHCs services. The infrastructure and core practices were able to partially mediate between the management practice and the quality of CHCs services. Nevertheless, the implementation of quality management still remained low in several targeted CHCs.